The Effect of Training and Development on Employees’ Performance in a Selected Call Centre in Kuala Lumpur, Malaysia - Kasturi, Rajasekar (2020)
The purpose of this research is to examine the effect of training needs assessment, training methods, training content, and employee development programs on employees’ performance. Data were collected using online survey through Google Form. The sample included 115 employees of a private call centre in Klang Valley. Statistical Package for Social Science (SPSS) was used to test the effect of independent variables on the dependent variable. Descriptive analysis was used to analyse the background of the respondents, whereas inferential statistics (Regression analysis) was used to analyse and test the hypotheses. Findings from this research showed that only training content and employee development programs had significant effect on employees’ performance, whereas training needs assessment and training methods did not show any significant effect on employees’ performance. Out of two independent variables that have significant effects, only training content showed positive effect on employees’ performance thus, supported the hypothesis postulated. The findings of this study suggested that training content should be given high attention whenever the management of the call centre decide to provide training to their employees as it could affect employees’ performance positively. Furthermore, this study was carried out in a single call centre, therefore the findings cannot be generalized to other call centres. Future research is hoped to extend the current scope of the research to include more call centres throughout the country.